Justice - Law, Cheryl (Wayland, Hove, 1993)
"Justice" by Cheryl Law and Kaye Stearman, published in 1993, is part of the "Human Rights" series. This 48-page book provides an in-depth study of the right to justice, using case studies of young people around the world. Some are denied justice because they are socially and economically disadvantaged, while others suffer from unjust legal systems in their countries. The book is illustrated with color and black-and-white photographs.